Hardware Requirements Analysis for Administrative Staff in Higher Education - Hafidz Sanjaya; Fajar Maula Hidayat (Universitas Majalengka, 2026)
The use of computer hardware that does not match workload requirements remains a common issue in higher education administrative activities, leading to reduced efficiency and productivity. This study aims to analyze hardware requirements for administrative staff at the Faculty of Psychology, Business, and Technology, Universitas Yayasan Pendidikan Imam Bonjol Majalengka, and to propose optimal hardware specifications. A case study approach was employed by evaluating three devices used by three staff members through observation and system performance assessment. The main contribution of this study lies in providing a workload-based hardware analysis supported by simple performance benchmarking to demonstrate the impact of hardware upgrades. The results indicate that existing systems, equipped with older mid-range processors, 4–8 GB RAM, and HDD storage, are insufficient to support multitasking and data processing efficiently. Performance testing shows that data input processing time, initially ranging from 10–12 minutes, can be reduced to 4–6 minutes using the recommended specifications. This represents an efficiency improvement of approximately 50–60% and a significant reduction in system latency. Therefore, this study offers a more measurable and evidence-based approach to hardware planning compared to conventional descriptive methods.